The Corporate Income Tax gap: A European approach to measuring losses in corporate tax revenues - Lidia Brun; Raffael Speitmann; Andrzej Leszek Stasio; Daniel Stoehlker (European Commission, Joint Research Centre (JRC), 2025)
This paper examines the Corporate Income Tax (CIT) compliance gap, the difference between revenue due under full compliance and actual collections, across 23 EU Member States, Norway, and Iceland. Existing bottom-up and top-down estimation methods each face notable limitations: bottom-up approaches are data-intensive and hard to harmonise, while top-down methods depend on uncertain adjustments for undeclared activity and cannot adequately capture multinational profit shifting. An implementation of the IMF RA-GAP top-down method in Spain illustrates these challenges, revealing substantial data needs, conceptual mismatches between national accounts and tax data, and reliance on unverifiable assumptions. To address these issues, the Joint Research Centre proposes a simplified top-down methodology based on Eurostat s exhaustiveness adjustments. This approach is transparent, reproducible, and feasible with data already reported by Member States. Applying it across countries reveals large variation in CIT gaps ranging from below 3% in high-compliance jurisdictions to above 20 35% in others with an unweighted average gap of 10.9% (around EUR 38 billion in 2017). Sectoral patterns consistently show higher gaps in informal, cash-intensive industries and lower gaps in regulated sectors. The paper concludes that while no single method captures all dimensions of non-compliance, the proposed approach offers a practical tool for regular EU-wide monitoring. Its effectiveness depends on the timely and harmonised publication of exhaustiveness adjustment data to support consistent CIT gap estimation and policy analysis.
Keywords: 330